Gut microbiota-derived short chain fatty acids are potential mediators in gut inflammation - Akhtar, Muhammad; Chen, Yan; Ma, Ziyu; Zhang, Xiaolong; Shi, Deshi; Khan, Jawaria A.; Liu, Huazhen (Animal Nutrition, 2022)
Gut inflammation is a challenging concern in humans and animals, which disturbs normal growth and leads to severe bowel diseases. Short chain fatty acids (SCFA) are the gut microbiota metabolites produced from fermentation of non-digestible carbohydrates, and have been reported to modulate gut inflammation. SCFA have been implicated as the potential therapeutic bioactive molecules for gut inflammatory diseases, and could be an alternative to antibiotic growth promoters (AGP). In this review, the existing knowledge about the types of SCFA, the related gut microbes producing SCFA, the roles of SCFA in maintaining gut homeostasis, and how SCFA modulate gut inflammation is summarized. The therapeutic application of SCFA in the treatment of inflammatory bowel disease (IBD) is also highlighted. [Display omitted]